Hubungan Pengetahuan dengan Kepatuhan Berobat Pasien Tuberkulosis - Saputri, Okti Tri; Rosyid, Fahrun Nur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine whether there is a relationship between knowledge about the side effects of tuberculosis drugs experienced by patients and compliance with treatment for tuberculosis patients. The method used in this research uses quantitative methods with a cross-sectional approach. The research results based on the Spearman Rank Correlation test obtained p-value = 0.000 < 0.05. In conclusion, the results obtained from this study show a relationship between knowledge about the side effects of Anti-Tuberculosis Drugs (OAT) and compliance with treatment for tuberculosis patients. Keywords: Treatment Compliance, Knowledge, Tuberculosis